Pesquisa de clima organizacional: uma análise crítica - Souza, Sonia Balmant Emerique de (2007)
The organization climate research is a widely used human resources tool grounded on the managerial discourse that preaches that listening to employees's opinions is relevant for the identification of corporate aspects that demand improvement. This study aims at desmistifying this discourse by means of analytical tools from the Critical Administration Studies, namely: denaturalized view of administration, detachment between intentions and performance and search for emancipation. The study is grounded on the assumption that the organizational climate research derives from functionalist theory, which benefits a dominating class, in name of productivity and for the maintenance of the status quo, therefore contributing for individual alienation at work. The study was designed to identify elements that show the relation between an organizational climate research tool and the social control over individuals in an organization - here the research conducted in 2005 by Centrais Elétricas Brasileiras S/A - Eletrobrás, the Brazilian power sector holding company. The theoretical section presents an overview of corporate paradigms relevant for a sound understanding of the organizational climate concept. Data analysis was conducted by means of the post-modern method of binary deconstruction: the questions contained in the tool's questionnaire were grouped into categories and then analyzed in terms of the fallowing conceptual pairs: well-being/productivity, autonomy/control, ethics/ competitiveness and participation/alienation. The analysis showed that the organization climate research tool is used as a resource for social control and power, because it contributes to individual alienation as it satisfies some specific individual demands, therefore preventing the individual form a thorough understanding of how the system works. Besides, the helps anticipate, mitigate and conceal the conflicts arising from the opposing interests of capital and labor.